Defying Straightforward Solutions: Emergence Studios as Ideal Incubators in Graduate Education and Beyond - Kari Eller; Gregory C.F. Dolezal; Erin Williams Benson; Younghyun Kim; Comfort Ninson; Brittani Hawk (Adult Education Research Conference, 2024)
Reimagining a classroom as an emergence studio, three groups of doctoral students used pragmatic imagination to tackle wicked problems through world building systems of action. This experience radically inspired their own constructive development and challenged conventional graduate education down to its rhizomatic roots. “What if?” they asked, believing that change is possible by defying straightforward solutions.
Keywords: Emergence studios; World building; Wicked Problems; Complexity; Graduate Education